SISTEM INFORMASI GEOGRAFIS PEMETAAN SEKOLAH MENENGAH KEJURUAN DI KABUPATEN LABUHANBATU MENGGUNAKAN WEBGIS - Lisma Zahara; Ibnu Rasyid Munthe; Ali Akbar Ritonga (STMIK Royal, 2021)
Abstract: Labuhanbatu Regency is a district that has many Vocational High Schools (SMK) which are very attractive to the community. Because each Vocational High School has its own vocational fields, for example Health, Automotive, Offices, and others. The existence of this Geographic Information System makes it easy for users to find Vocational High School routes. Vocational High Schools are schools that make students or prospective students even more skilled. In making this Geographic Information System requires Systems Development Life Cycle to analyze gradually, and Webgis to display maps as well as GPS to ascertain the location of the earth's surface and use UML design such as activity diagrams, sequence diagrams, and usecase. There is also a waterfall method in making this Geographic Information System such as its analysis, implementation, design, maintenance and also the testing phase. The Testing Phase uses the BlackBox to test the system whether it is running well or not and is suitable for use by users. Keywords: BlackBox Testing; Geographic Information System; Google Maps; GPS; UML; Vocational High School Abstrak: Kabupaten Labuhanbatu termasuk kabupaten yang memiliki banyak Sekolah Menengah Kejuruan (SMK) yang sangat diminati masyarakat. Karena setiap SMK memiliki kejuruan masing-masing dalam bidangnya misalkan Kesehatan, Otomotif, Perkantoran, dan lain-lain. Adanya Sistem Informasi Geografi ini memudahkan para pengguna untuk mencari rute Sekolah Menengah Kejuruan. Sekolah Menengah Kejuruan adalah sekolah yang menjadikan para siswa atau calon siswa lebih trampil lagi. Dalam pembuatan Sistem Informasi Geografi ini memerlukan Systems Development Life Cycle menganalisis secara bertahap, dan Webgis untuk menampilkan peta juga GPS untuk memastikan letak permukaan bumi dan menggunakan Perancangan UML seperti activity diagram, sequence diagram, dan usecase. Terdapat juga Metode waterfall dalam membuat Sistem Informasi Geografi ini seperti analisanya, implementasi, desain, pemeliharaan dan juga tahap pengujian. Tahap Pengujian menggunakan BlackBox untuk menguji Sistem apakah berjalan baik atau tidak dan sudah layak digunakan bagi pengguna. Kata kunci: Sekolah Menengah Kejuruan; GPS; Peta Google; Sistem Informasi Geografi; Uji BlackBox; UML